Penyebab Resistensi Obat Tuberkulosis - Parlaungan, Jansen; Tambunan, Sulastri GP; Djamanmona, Rolyn Frisca; Purwana, Eka Rudy; Mobalen, Oktovina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the causes of drug resistance in patients with pulmonary TB at Sele Be Solu General Hospital, Sorong City. The research method used is quantitative research. The results showed that the most dominant reason for not taking medication routinely was not being able to tolerate the side effects, namely 9 respondents (5.9%), then the treatment period felt long, namely 7 respondents (4.6%), often forgetting, 7 respondents (4.6%), then not routinely seeking treatment at health service facilities (Fasyankes) namely 5 people (3.3%), then feeling healthy, namely 4 respondents (2.6%), and those who had no complaints, namely 121 respondents (79.1%). In conclusion, the factors that often occur in patients with pulmonary TB at Sele Be Solu General Hospital are caused by patients not complying with the advice of doctors or health workers, not regularly taking OAT guidelines, stopping treatment unilaterally before time, and having drug absorption disorders, as well as other reasons because some patients are far from health service facilities due to distance factors, especially patients from outside Sorong City. Keywords: Causes, Drug Resistance, Tuberculosis